ANALISIS EFISIENSI BANK PERKREDITAN RAKYAT DI WILAYAH JABODETABEK DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS - Imam Hartono; Setiadi Djohar; Heny K. Daryanto (School of Business, Bogor Agricultural University (SB-IPB), 2008)
The research was conducted to measure rural banks (BPR) efficiency level in Jabodetabek and also to identify factors that increase the efficiency level. The measurement was done using non parametric approach with Data Envelopment Analysis. The result indicated that rural banks in Jabodetabek area were in inefficient condition, 80% of rural banks observed were inefficient both in technical and scale. Measurement on several asset distribution showed rural banks had efficiency scale on certain business scale, rural banks with total asset between Rp.1 – Rp.10 billion had the highest efficiency scale and rural banks with total asset less than Rp.500 million had the lowest efficiency scale. Potential improvement analysis result with CCR and BCC models showed that other income was the most contributed output variable to increase 30% to 40 % of rural banks efficiency level. Meanwhile, measurement using BCC model showed that, from output side, current asset has contributed to increased rural banks efficiency level by raising revenue from current asset management up to 10% from average value in 2007. On input side, all input variable had the same potential improvement value which increased the efficiency level by reducing labor cost, fixed asset cost, and the cost of fund 17%-18% from average value in 2007.